PERENCANAAN PERSIMPANGAN JL. PANGERAN SURYANATA - JL. HM. ARDAN - JL. RING ROAD DI KOTA SAMARINDA - RAHMAN, ARIF (KURVA S JURNAL MAHASISWA, 2014)
Arif Rahman, NPM : 10.11.1001.7311.219, PlaningJunctionStreetPangeranSuryanata-StreetHM. Ardan-StreetRing RoadInCitySamarinda, Pembimbing I : Dr. Ir. Hendrik Sulistio, MT. dan Pembimbing II : Rossa Agustaniah, ST, MT Development of the transport sector which is one of supporting the economy of a bias derah not be separated from the development of the region, as well as an increase in the frequency of activity and mobility of society due to increased incomes. This increase should be offset by the availability of infrastructure and management. If this continues without peyiapan adequate road infrastructure, poor utilization of the road and traffic management are not optimal and ethical berlalulintas for road users who are less, then the vehicle traffic on these roads will certainly become unmanageable and congestion into everyday problems.As the intersection of several roads meeting is a critical point on the road network. At this critical section, the potential problems that can occur with a number of meetings described some of the current movement of vehicles in different directions at the same point disimpang. The movement primarily toward the vehicle swerved to the right and straight are conflicts cause congestion and accidents.This conflicts that affect both the poor performance of an intersection.The purpose of this study is as follows: 1. Knowing the visibility at the intersection Plan2. Knowing Taper Plan at the intersection3. Knowing the Right Turn Lane Plan4. Knowing Planning Left Turn Lane From the analysis of Interchange Planning Jl. Prince Suryanata - Jl. HM. Ardan - Jl. Ring Road in thecity of Samarinda concluded: Visibility at intersections in accordance with the speed of the plan is closely related to the visibility at an intersection, and the speed that will be used at this intersection is at 40 km / h, which has entered visibility along the 100 m and safe visibility along 60 m.Long Taper at the intersection is the length of taper (lt) selected among the greatest deceleration lane minimum length (ld) and a minimum length of lane shifts (lc) is approximately 24 meters.The length of the queue lane turn right at the intersection of these studies (without traffic lights) is calculated based on the number of vehicles entering the intersection of every two minutes during peak hours, the importance of each arm are: PendekatAverage number of vehicles Turn Right (M) ( veh / min ) The distance between the average vehicle (S) ( meters )Queue Length Turn Right ( ls ) ( meters ) B5660D4648A3636C4648 The length ofthe queuelaneturn leftatthe intersection ofthesestudies(without traffic lights) onthe same principle asthe calculation ofthe vehicleturn right, is calculatedwiththe followingformula, based on the numberof vehicles enteringthe intersectionevery2minutesduring rush hour. PendekatAverage number of vehicles Turn Right (M) ( veh / min )The distance between the average vehicle (S) ( meters )Queue Length Turn Right ( ls ) ( meters )B5660D3636A6672C3636 The sizeof themedian ofthe road, rumaja, rumijaandruwasjaareasfollows: Use of Roads Unit ( m )Median width min , ( m )[ median width including the shoulder width , the width of the edge of the edge line markings including the shoulder ] be elevated1.50 ; elevated as high as kereb to speed plans < 60 km / h and into 1.80 if the median is used shanties crossings . Configuring the shoulder width + height separator building kereb + shoulder in : 0.50 + 0.50 + 0.50 and 0.50 + 0.80 + 0.50 if used shanties crossings .The pavement width(m) 1,00Rumaja min, (m)Widht (m)24 High (m)5 In The (m)1,5Rumija min,  (m) 25Ruwasja min, (m) 15